Examining the trade-off between structural, mechanical properties and shielding performance of Pr2O3-enhanced 316L stainless steel - Yayla, Nihal; Albayrak, Muhammet Gokhan; Guler, Omer; Sen Baykal, Duygu; Alkarrani, Hessa; ALmisned, Ghada; Tekin, H. O. (Elsevier Sci Ltd, 2025)
This study explores the structural, mechanical, and radiation shielding properties of 316L stainless steel composites reinforced with varying weight percentages of Pr2O3. The aim is to enhance radiation attenuation capabilities while maintaining structural integrity for nuclear applications. The composites were fabricated using the mechanical alloying method, followed by detailed characterization through X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. Key radiation shielding parameters, including mass attenuation coefficient, linear attenuation coefficient, half-value layer, and effective atomic number, and transmission factor values were analysed using theoretical and computational models. Additionally, elastic modulus calculations were performed to assess mechanical properties. The results indicate that incorporating Pr2O3 significantly enhances shielding performance. The 316L-SS%20Pr(2)O(3) composite exhibited the highest mass and linear attenuation coefficients values, with a notable reduction in half value layer values compared to the unreinforced 316L stainless steel. At lower photon energies, effective atomic number improved by 39.3 % for the 316L-SS%20Pr(2)O(3) sample, while neutron shielding efficiency also increased. However, the elastic modulus decreased with higher Pr2O3 content, reflecting a trade-off between mechanical stiffness and radiation shielding efficiency. The findings demonstrate that 316L-SS%20Pr(2)O(3) is a promising material for applications requiring superior radiation shielding, particularly in environments where mechanical load is secondary.
Keywords: 316L-stainless steel; Alloys; Radiation shielding; Composites